Preparation method and application of microwave-assisted 3D cross-linked molecular template organic carbon
Patent Information
- Application Number
- CN202611461806.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明针对现有技术中活性炭在二次利用过程中比表面积减小、吸附位点流失,以及改性活性炭靶向吸附性能差、再生稳定性不足等缺陷,本发明提供一种微波辅助3D交联分子模板有机质碳的制备方法,同时提供该有机质碳经再生后应用于焦炉煤气中靶向有机硫(苯并噻吩)脱除的方法,实现苯并噻吩的高效、靶向脱除,且吸附剂再生后性能稳定,可多次循环利用
[0035]本发明的优点及其积极效果是。
Smart Images

Figure CN122977382A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic sulfur removal technology, and in particular relates to a method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates and its application. Background Technology
[0002] Coke oven gas, an important byproduct of the iron and steel and coal chemical industries, is rich in combustible components such as hydrogen and methane, making it a highly valuable clean energy source. However, coke oven gas contains various organic sulfur pollutants, among which benzothiophene, a typical difficult-to-remove organic sulfur compound, is highly stable and not easily adsorbed by conventional adsorbents. Its presence not only corrodes downstream production equipment and poisons catalysts but also generates SO₂ during combustion. x The removal of benzothiophene from coke oven gas is a harmful gas that causes environmental pollution. Therefore, the targeted removal of benzothiophene from coke oven gas has important industrial significance and environmental value.
[0003] Currently, the mainstream technologies for removing organic sulfur from coke oven gas include adsorption, catalytic hydrogenation, and oxidation. Among these, adsorption is widely used in industrial production due to its advantages such as simple operation, low cost, and no secondary pollution. Activated carbon, as a commonly used adsorbent, has the characteristics of large specific surface area, rich pore structure, and excellent adsorption performance. However, it has significant drawbacks in practical applications: after multiple adsorption-regeneration cycles, the pore structure of activated carbon is prone to collapse, the specific surface area is significantly reduced, and a large number of adsorption sites are lost, resulting in a significant decrease in adsorption capacity. This makes it difficult to achieve efficient secondary utilization and increases the cost of industrial applications.
[0004] To improve the regeneration performance and adsorption stability of activated carbon, existing technologies often employ methods such as metal ion modification and acid-base modification. However, the modified activated carbon still suffers from the following shortcomings: First, the active groups are not sufficiently exposed during the modification process, resulting in a limited number of adsorption sites and poor targeted adsorption performance. Second, the binding force between metal ions and activated carbon is weak, making them prone to loss during regeneration and unable to maintain long-term framework stability. Third, the regeneration process requires high temperatures or long periods of time, which not only consumes a lot of energy but also easily damages the pore structure of activated carbon, further reducing its secondary adsorption performance.
[0005] Therefore, developing an adsorbent with a simple preparation process, low cost, high specific surface area, abundant adsorption sites, and excellent regeneration performance, capable of targeted removal of benzothiophene from coke oven gas, and solving the technical problem of reduced specific surface area and adsorption sites in the secondary utilization of existing activated carbon, has become an urgent technical problem to be solved in this field. Summary of the Invention
[0006] This invention addresses the shortcomings of existing technologies, such as reduced specific surface area and loss of adsorption sites during the secondary utilization of activated carbon, as well as poor targeted adsorption performance and insufficient regeneration stability of modified activated carbon. This invention provides a method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates, and also provides a method for applying the regenerated organic carbon to the targeted removal of organic sulfur (benzothiophene) from coke oven gas, achieving efficient and targeted removal of benzothiophene, and ensuring stable performance of the adsorbent after regeneration, allowing for multiple recycling.
[0007] To solve the above technical problems, the technical solution adopted in this invention is: a method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates, which is carried out according to the following steps:
[0008] Step S1, Raw material pretreatment: Select walnut shells as biomass raw materials, remove impurities and clean them, then dry them in an oven at 60-80℃ until constant weight, and then use flash extraction technology to pulverize the dried walnut shells at the molecular level to obtain a walnut shell molecular suspension.
[0009] Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular suspension obtained in step S1, and stir and mix in a constant temperature environment of 25-35℃ for 10-20 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder.
[0010] Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer and stirred for 30-60 minutes at 25-35℃ and a stirring rate of 200-300 r / min, allowing the FeSO4 solution to crosslink. 2+ A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder;
[0011] Step S4, Microwave Carbonization Molding: The crosslinking system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in an oven at 60-80℃ and dried to constant weight. It is then ground to a particle size of 100-200 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under the conditions of microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D crosslinked molecular template organic carbon.
[0012] Furthermore, the pulverization parameters of the flash extraction technology in step S1 are: flash extraction speed 15000 r / min, pulverization time 5-10 min.
[0013] Furthermore, the mass ratio of K2CO3 to walnut shell molecular-level powder is 1:3-1:5.
[0014] Furthermore, the mass ratio of FeSO4 to walnut shell molecular-level powder is 1:10-1:15, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:20-1:30.
[0015] A preferred method for preparing microwave-assisted 3D cross-linked molecular template organic carbon is carried out according to the following steps:
[0016] Step S1, Raw material pretreatment: Walnut shells are selected as biomass raw materials. After removing impurities and cleaning, they are placed in a 70℃ oven and dried to constant weight. Then, the dried walnut shells are molecularly pulverized using flash extraction technology to obtain a walnut shell molecular suspension. The flash extraction speed is 15000 r / min and the pulverization time is 8min.
[0017] Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular-level suspension obtained in step S1. The mass ratio of K2CO3 to walnut shell molecular-level powder is 1:4. Stir and mix in a constant temperature environment of 30℃ for 15 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder.
[0018] Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:12, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:25. The mixture is stirred for 45 minutes at 30°C and a stirring rate of 250 r / min to allow the FeSO4 solution to crosslink with the walnut shell molecular-level powder to form a crosslinked structure. 2+ A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder;
[0019] Step S4, Microwave Carbonization Molding: The cross-linked system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in a 70°C oven to dry to constant weight and ground to a particle size of 150 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D cross-linked molecular template organic carbon.
[0020] A preferred method for preparing microwave-assisted 3D cross-linked molecular template organic carbon is carried out according to the following steps:
[0021] Step S1, Raw material pretreatment: Walnut shells are selected as biomass raw materials. After removing impurities and cleaning, they are placed in a 60℃ oven and dried to constant weight. Then, the dried walnut shells are molecularly pulverized using flash extraction technology to obtain a walnut shell molecular suspension. The flash extraction speed is 15000 r / min and the pulverization time is 5min.
[0022] Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular-level suspension obtained in step S1. The mass ratio of K2CO3 to walnut shell molecular-level powder is 1:3. Stir and mix in a constant temperature environment of 25°C for 10 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder.
[0023] Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:10, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:20. The mixture is stirred for 30 minutes at 25°C and a stirring rate of 200 r / min to allow the FeSO4 solution to crosslink with the walnut shell molecular-level powder to form a crosslinked structure. 2+ A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder;
[0024] Step S4, Microwave Carbonization Molding: The crosslinking system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in a 60°C oven to dry to constant weight and ground to a particle size of 100 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D crosslinked molecular template organic carbon.
[0025] A preferred method for preparing microwave-assisted 3D cross-linked molecular template organic carbon is carried out according to the following steps:
[0026] Step S1, Raw material pretreatment: Walnut shells are selected as biomass raw materials. After removing impurities and cleaning, they are placed in an 80℃ oven to dry to constant weight. Then, the dried walnut shells are molecularly pulverized using flash extraction technology to obtain a walnut shell molecular suspension. The flash extraction speed is 15000 r / min and the pulverization time is 10 min.
[0027] Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular-level suspension obtained in step S1. The mass ratio of K2CO3 to walnut shell molecular-level powder is 1:5. Stir and mix in a constant temperature environment of 35℃ for 20 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder.
[0028] Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:15, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:30. The mixture is stirred for 60 minutes at 35°C and a stirring rate of 300 r / min to allow the FeSO4 solution to crosslink with the walnut shell molecular-level powder to form a 3D crosslinked structure. 2+ A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder;
[0029] Step S4, Microwave Carbonization Molding: The crosslinking system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in an 80°C oven to dry to constant weight and ground to a particle size of 200 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D crosslinked molecular template organic carbon.
[0030] Another technical solution to be protected by this invention: the application of microwave-assisted 3D cross-linked molecular template organic carbon, which is carried out according to the following steps:
[0031] Step D1, Targeted Adsorption and Removal: The microwave-assisted 3D cross-linked molecular template organic carbon prepared above is filled into the adsorption column. The coke oven gas is controlled to pass through the adsorption column at a flow rate of 1-3 mL / min, the adsorption temperature is 25-35℃, and the pressure is atmospheric pressure. Benzothiophene in the coke oven gas is targeted and adsorbed by the active adsorption sites on the surface of the biochar through the molecular channels reserved by the molecular template, thereby achieving the removal of organic sulfur in the coke oven gas.
[0032] Step D2, Adsorbent Regeneration: When the organic carbon of the microwave-assisted 3D cross-linked molecular template reaches adsorption saturation, the coke oven gas is stopped. The microwave reactor is connected to the adsorption column, and the saturated biomass in the adsorption column is irradiated with 1000W microwave for 1-2 minutes. The strong absorption performance of Fe ions on microwaves is used to rapidly raise the local temperature of the biomass to 200-300℃, removing the benzothiophene adsorbed on the surface of the biomass. The removed benzothiophene is recovered by condensation, realizing resource recycling.
[0033] Step D3, Recycling: After regeneration is complete, microwave irradiation is stopped. After the adsorption column cools to room temperature, coke oven gas is introduced again, and steps D1-D2 are repeated to achieve multiple recycling of organic carbon from microwave-assisted 3D cross-linked molecular templates.
[0034] Preferably, in step 1, the ratio of the amount of organic carbon in the microwave-assisted 3D cross-linked molecular template to the amount of coke oven gas processed is 1g:50-100L.
[0035] The advantages and positive effects of this invention are as follows.
[0036] 1. This invention solves the technical problems of reduced specific surface area and loss of adsorption sites during the secondary utilization of activated carbon. It employs flash extraction technology to molecularly pulverize walnut shells, fully exposing hydrophilic active groups such as phenolic hydroxyl and carboxyl groups. Combined with K2CO3 protonation treatment to provide sufficient cross-linking sites, and then through Fe... 2+ The three-dimensional network structure formed by coordination and cross-linking with active groups has a stable pore structure. The Fe cross-linked three-dimensional biochar formed after microwave carbonization has a stable pore structure. The skeletal cross-linking effect of Fe ions can effectively prevent the collapse of the pore structure during the regeneration process, and retain the effective pore area and adsorption sites.
[0037] 2. This invention enables targeted and efficient adsorption of benzothiophene. By pre-adding the target pollutant benzothiophene as a molecular template during the preparation process, molecular channels matching the benzothiophene molecular structure are reserved during biochar formation. Simultaneously, Fe... 2+ The coordination with phenolic hydroxyl and carboxyl groups forms specific adsorption sites for benzothiophene, which greatly improves the targeted adsorption performance of the adsorbent for benzothiophene.
[0038] 3. The adsorbent exhibits high regeneration efficiency, low energy consumption, and stable performance. The addition of Fe ions not only plays a role in skeletal cross-linking but also significantly enhances the microwave absorption performance of biochar. During the regeneration process, microwave irradiation can rapidly raise the local temperature of the biochar, completing the removal of benzothiophene within 1-2 minutes. Furthermore, the entire system does not require high-temperature heating during the regeneration process. The specific surface area and adsorption sites of the regenerated biochar are well preserved, allowing for multiple recycling and reducing industrial application costs.
[0039] 4. The overall preparation process of this invention is simple, environmentally friendly, and low-cost. Using walnut shells as biomass raw material is widely available and renewable, reducing raw material costs. The preparation process requires no complex equipment and is simple in steps, meeting the needs of green and environmentally friendly industrial development. The short microwave carbonization time (only 1 minute) further reduces energy consumption.
[0040] 5. This invention achieves resource recycling. The benzothiophene removed during the regeneration process can be recovered through condensation, avoiding secondary pollution and realizing the resource utilization of pollutants; the adsorbent can be recycled multiple times, further improving the economic and environmental benefits of the process. Attached Figure Description
[0041] Figure 1 This is a process flow diagram for the preparation of organic carbon using microwave-assisted 3D cross-linked molecular templates.
[0042] Figure 2 The image shows a scanning electron microscope (SEM) image of Fe cross-linked three-dimensional biochar prepared in Embodiment 3 of the present invention, wherein (a) is Fe cross-linked three-dimensional biochar and (b) is conventional walnut shell biochar.
[0043] Figure 3 This is a comparison chart of the adsorption capacity of Fe cross-linked three-dimensional biochar prepared in Embodiment 3 of the present invention and conventional activated carbon. Detailed Implementation
[0044] To make the objectives, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below.
[0045] Example 1
[0046] The preparation of organic carbon using microwave-assisted 3D cross-linked molecular templates is carried out according to the following steps:
[0047] Step S1, Raw Material Pretreatment: Walnut shells were selected as the biomass raw material. Impurities such as stones and sawdust were removed, and the shells were washed three times with deionized water. They were then dried in a 60℃ oven to constant weight. Subsequently, a flash extraction technique was used to perform molecular-level pulverization of the dried walnut shells, resulting in a walnut shell molecular-level suspension. The flash extraction parameters were: flash extraction speed 15000 r / min, pulverization time 5 min, which ensured the full exposure of hydrophilic active groups such as phenolic hydroxyl and carboxyl groups contained in the walnut shells.
[0048] Step S2, Protonation and Crosslinking Site Pretreatment: A K₂CO₃ solution was added to the walnut shell molecular-level suspension obtained in Step S1, and the mixture was stirred at 25°C for 10 minutes to allow the K₂CO₃ to protonate the hydrophilic active groups in the walnut shell powder. The mass ratio of K₂CO₃ to walnut shell molecular-level powder was 1:3. The protonation reaction promotes the dissolution and dispersion of the walnut shell powder in the subsequent system and provides sufficient crosslinking sites for the subsequent crosslinking reaction.
[0049] Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer and stirred for 30 minutes at 25°C and a stirring rate of 200 r / min, allowing the FeSO4 solution to crosslink with the target pollutant. 2+ A three-dimensional network cross-linked structure is constructed through coordination cross-linking reactions of the exposed phenolic hydroxyl and carboxyl groups in walnut shell powder. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:10, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:20. Benzothiophene is added beforehand as a molecular template, which reserves molecular channels that match the benzothiophene molecular structure during the formation of the three-dimensional network structure.
[0050] Step S4, Microwave Carbonization Molding: The cross-linked system obtained in Step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. The filter residue is then dried in a 60℃ oven to constant weight and ground to a particle size of 100 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment at a microwave power of 1000W and a microwave irradiation time of 1 min to obtain microwave-assisted 3D cross-linked molecular template organic carbon (Fe cross-linked three-dimensional biomass carbon). Microwave irradiation can rapidly achieve biomass carbonization while fixing the three-dimensional network structure and preserving the molecular channels and active adsorption sites reserved in the molecular template.
[0051] Example 2
[0052] The preparation of organic carbon using microwave-assisted 3D cross-linked molecular templates is carried out according to the following steps:
[0053] Step S1, Raw Material Pretreatment: Walnut shells were selected as the biomass raw material. Impurities such as stones and sawdust were removed, and the shells were washed three times with deionized water. They were then dried in an 80℃ oven to constant weight. Subsequently, a flash extraction technique was used to perform molecular-level pulverization of the dried walnut shells, resulting in a walnut shell molecular-level suspension. The flash extraction parameters were: flash extraction speed 15000 r / min, pulverization time 10 min, which ensured that the hydrophilic active groups such as phenolic hydroxyl and carboxyl groups contained in the walnut shells were fully exposed.
[0054] Step S2, Protonation and Crosslinking Site Pretreatment: A K₂CO₃ solution was added to the walnut shell molecular-level suspension obtained in Step S1, and the mixture was stirred at 35°C for 20 minutes to allow the K₂CO₃ to protonate the hydrophilic active groups in the walnut shell powder. The mass ratio of K₂CO₃ to walnut shell molecular-level powder was 1:5. The protonation reaction promotes the dissolution and dispersion of the walnut shell powder in the subsequent system and provides sufficient crosslinking sites for the subsequent crosslinking reaction.
[0055] Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer and stirred for 60 minutes at 35°C and a stirring rate of 300 r / min to allow the FeSO4 solution to crosslink. 2+ A three-dimensional network cross-linked structure is constructed through coordination and cross-linking reactions of the exposed phenolic hydroxyl and carboxyl groups in walnut shell powder. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:15, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:30. Benzothiophene is added beforehand as a molecular template, which reserves molecular channels that match the benzothiophene molecular structure during the formation of the three-dimensional network structure.
[0056] Step S4, Microwave Carbonization: The cross-linked system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. The filter residue is then dried in an 80℃ oven to constant weight and ground to a particle size of 200 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment at a microwave power of 1000W and a microwave irradiation time of 1 min to obtain microwave-assisted 3D cross-linked molecular template organic carbon (Fe cross-linked three-dimensional biomass carbon). Microwave irradiation can rapidly achieve biomass carbonization while fixing the three-dimensional network structure and preserving the molecular channels and active adsorption sites reserved in the molecular template.
[0057] Example 3
[0058] Step S1, Raw material pretreatment: Walnut shells are selected as biomass raw materials. After removing impurities and cleaning, they are placed in a 70℃ oven and dried to constant weight. Then, the dried walnut shells are molecularly pulverized using flash extraction technology to obtain a walnut shell molecular suspension. The flash extraction speed is 15000 r / min and the pulverization time is 8min.
[0059] Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular-level suspension obtained in step S1. The mass ratio of K2CO3 to walnut shell molecular-level powder is 1:4. Stir and mix in a constant temperature environment of 30℃ for 15 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder.
[0060] Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:12, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:25. The mixture is stirred for 45 minutes at 30°C and a stirring rate of 250 r / min to allow the FeSO4 solution to crosslink with the walnut shell molecular-level powder to form a crosslinked structure. 2+A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder;
[0061] Step S4, Microwave Carbonization Molding: The cross-linked system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in a 70°C oven to dry to constant weight and ground to a particle size of 150 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D cross-linked molecular template organic carbon.
[0062] Example 4
[0063] The preparation of organic carbon using microwave-assisted 3D cross-linked molecular templates is carried out according to the following steps:
[0064] Step S1, Raw Material Pretreatment: Walnut shells were selected as the biomass raw material. Impurities such as stones and sawdust were removed, and the shells were washed three times with deionized water. They were then dried in a 75℃ oven to constant weight. Subsequently, a flash extraction technique was used to perform molecular-level pulverization of the dried walnut shells, resulting in a walnut shell molecular-level suspension. The pulverization parameters for the flash extraction technique were: flash extraction speed 15000 r / min, pulverization time 9 min, which ensured that the hydrophilic active groups such as phenolic hydroxyl groups and carboxyl groups contained in the walnut shells were fully exposed.
[0065] Step S2, Protonation and Crosslinking Site Pretreatment: Add K₂CO₃ solution to the walnut shell molecular-level suspension obtained in Step S1, and stir at 33°C for 10-20 min to allow the K₂CO₃ to protonate the hydrophilic active groups in the walnut shell powder. The mass ratio of K₂CO₃ to walnut shell molecular-level powder is 1:4.5. The protonation reaction promotes the dissolution and dispersion of the walnut shell powder in the subsequent system and provides sufficient crosslinking sites for the subsequent crosslinking reaction.
[0066] Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer and stirred for 50 minutes at 33°C and a stirring rate of 280 r / min to allow the FeSO4 solution to crosslink. 2+ A three-dimensional network cross-linked structure is constructed through coordination cross-linking reactions of the exposed phenolic hydroxyl and carboxyl groups in walnut shell powder. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:14, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:28. Benzothiophene is added beforehand as a molecular template, which reserves molecular channels that match the benzothiophene molecular structure during the formation of the three-dimensional network structure.
[0067] Step S4, Microwave Carbonization: The cross-linked system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. The filter residue is then dried in a 75℃ oven to constant weight and ground to a particle size of 180 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment at a microwave power of 1000W and a microwave irradiation time of 1 min to obtain Fe cross-linked three-dimensional biomass char (microwave-assisted 3D cross-linked molecular template organic carbon). Microwave irradiation can rapidly achieve biomass carbonization while fixing the three-dimensional network structure and preserving the molecular channels and active adsorption sites reserved by the molecular template.
[0068] Comparative Example 1
[0069] This comparative example uses a conventional method to prepare walnut shell activated carbon. The specific steps are as follows: after removing impurities, washing and drying the walnut shells, they are pulverized to 150 mesh using a common pulverizer, placed in a muffle furnace, and carbonized at 500°C for 2 hours under a nitrogen atmosphere to obtain conventional walnut shell activated carbon; benzothiophene adsorption and regeneration tests are performed according to the method in Example 2.
[0070] As shown in Figure 2(a), the Fe-crosslinked three-dimensional biochar prepared in Example 3 of this invention exhibits a typical hierarchical porous three-dimensional network structure. Microscopic morphology reveals a high surface roughness with numerous interconnected mesopores and macropores. This open three-dimensional framework structure facilitates the rapid diffusion and transport of adsorbate molecules. Furthermore, uniformly distributed nanoparticles (corresponding to Fe species) can be observed on the carbon framework surface and within the pores. These particles are anchored to the carbon matrix through chemical crosslinking, not only avoiding pore blockage but also serving as active centers to further enrich the surface chemical properties, thus supporting the framework and preventing excessive shrinkage of micropores during activation.
[0071] In contrast, the morphology of conventional walnut shell biochar (without Fe crosslinking treatment) shown in Figure 2(b) appears more dense and disordered. Its surface is relatively smooth, lacking effective mesoporous channel connections, exhibiting a state of local collapse or accumulation. This structure easily leads to pore blockage during adsorption, limiting the utilization of internal specific surface area, and during desorption and regeneration, irreversible pore closure easily occurs due to the lack of a three-dimensional support structure.
[0072] In summary, Figure 2 The SEM comparison clearly demonstrates that the Fe crosslinking strategy successfully constructed a three-dimensional porous structure with excellent connectivity. This structural difference directly explains the higher adsorption capacity and better cycling stability exhibited by the material of this invention: the three-dimensional interconnected channels reduce mass transfer resistance, while the crosslinking effect of Fe species ensures structural integrity during long-term operation.
[0073] The organic carbon from Example 3 and Comparative Example 1 was applied to the removal of benzothiophene from coke oven gas. The specific removal process is as follows:
[0074] Step D1, Targeted Adsorption and Removal: Weigh 5g of the Fe cross-linked three-dimensional biochar prepared in Example 3 / walnut shell activated carbon from Comparative Example 1, and fill it into an adsorption column with an inner diameter of 10mm and a length of 100mm; simulated coke oven gas (with a benzothiophene concentration of 2mg / L, and the remaining components being H2 58.77 vol%, CH4 26.70 vol%, CO 8.09 vol%, N2 3.58 vol%, O2 0.82 vol%, CO2 2.04 vol%). The benzothiophene in the coke oven gas was introduced into the adsorption column at a flow rate of 115 mL / min and an adsorption temperature of 30℃. Benzothiophene in the coke oven gas was targeted and adsorbed by the active adsorption sites on the surface of the biochar through molecular channels reserved in the molecular template, thus achieving the removal of organic sulfur from the coke oven gas. The concentration of benzothiophene in the coke oven gas after adsorption was detected by gas chromatography, and the adsorption capacity was calculated. The adsorption capacity was found to be 128.5 mg / g, which is 28.2% higher than that of conventional walnut shell activated carbon (adsorption capacity 100.2 mg / g).
[0075] Step D2, Adsorbent Regeneration: When the organic carbon of the microwave-assisted 3D cross-linked molecular template reaches adsorption saturation (the concentration of benzothiophene at the adsorption column outlet reaches 3.75 × 10⁻⁶), the adsorbent is regenerated. -4 (mg / L (0.1 ppmv)) Stop the flow of coke oven gas, connect the microwave reactor to the adsorption column, and use 1000W microwave irradiation on the saturated biochar in the adsorption column for 1.5 min. Utilize the strong absorption performance of Fe ions on microwaves to rapidly raise the local temperature of the biochar to 200-300℃, remove the benzothiophene adsorbed on the surface of the biochar, and recover the removed benzothiophene by condensation.
[0076] Step D3, Recycling: After regeneration is complete, stop microwave irradiation and wait for the adsorption column to cool to room temperature (30°C) before introducing coke oven gas again and repeating steps D1-D2.
[0077] Combination Figure 3 As shown in the comparison with the original data, the Fe cross-linked three-dimensional biochar prepared in this invention is significantly superior to conventional activated carbon in both adsorption performance and cycle stability. In the initial adsorption stage, the saturated sulfur capacity of the material in this invention reaches as high as 128.5 mg / g, which is 28.2% higher than that of conventional activated carbon (100.2 mg / g), breaking through the performance bottleneck of approximately 100 mg / g for conventional coal-based mesoporous carbon with a specific surface area of 1000 m² / g.
[0078] More importantly, after five adsorption-desorption cycles, the adsorption capacity of the material of this invention remained at 116.5 mg / g, with a capacity retention rate of 90.7%; while the capacity of conventional activated carbon decreased to 75.5 mg / g, with a retention rate of only 75.3%. It is noteworthy that the remaining adsorption capacity of the material of this invention after the fifth cycle (116.5 mg / g) was even higher than the initial adsorption capacity of conventional activated carbon (100.2 mg / g). This data strongly demonstrates that the three-dimensional network structure constructed by Fe crosslinking not only provides abundant active sites but also effectively inhibits pore collapse and active site loss during the cycling process, endowing the material with excellent regeneration and reuse performance.
[0079] Table 1 Pore structure data for AC1 and AC2
[0080] Note: AC1 is the data before use of Fe cross-linked three-dimensional biochar; AC2 is the data after 5 cycles.
[0081] Comparing the pore structure data of AC1 (before use) and AC2 (after 5 cycles) in Table 1, it can be seen that the Fe cross-linked three-dimensional biochar of this invention still exhibits excellent structural stability after undergoing multiple adsorption-desorption cycles. Specifically, after cycling, the BET specific surface area of the material slightly decreased from 1430.2 m² / g to 1395.8 m² / g, with a retention rate as high as 97.6%; the total pore volume decreased from 0.890 cm³ / g to 0.778 cm³ / g, mainly due to changes in the flux of some mesopores, but the core micropore volume still retained 92.2% (from 0.773 cm³ / g to 0.713 cm³ / g).
[0082] Notably, the proportion of micropores actually increased from 86.82% to 91.67% after cycling, indicating that the Fe cross-linked three-dimensional network effectively supported the microporous structure, preventing the collapse or blockage of micropores during cycling and preferentially preserving highly active microporous adsorption sites. The average pore size was fine-tuned from 2.68 nm to 2.49 nm, further confirming the integrity of the material's main pore structure.
[0083] Experiments have verified that this invention uses flash extraction technology to achieve molecular-level pulverization of walnut shells, combined with K2CO3 protonation and Fe... 2 + The 3D network structure is constructed through coordination crosslinking, and targeted adsorption channels are reserved using benzothiophene as a molecular template, solving the problem of performance degradation after activated carbon regeneration. Moreover, the Fe crosslinked three-dimensional biochar of this invention has strong targeted adsorption performance, high regeneration efficiency, low energy consumption, good cycle stability, and an environmentally friendly and inexpensive preparation process, which can achieve efficient removal of benzothiophene from coke oven gas and resource recycling.
[0084] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.
Claims
1. A method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates, characterized in that: Follow these steps: Step S1, Raw material pretreatment: Select walnut shells as biomass raw materials, remove impurities and clean them, then dry them in an oven at 60-80℃ until constant weight, and then use flash extraction technology to pulverize the dried walnut shells at the molecular level to obtain a walnut shell molecular suspension. Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular suspension obtained in step S1, and stir and mix in a constant temperature environment of 25-35℃ for 10-20 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder. Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer and stirred for 30-60 minutes at 25-35℃ and a stirring rate of 200-300 r / min, allowing the FeSO4 solution to crosslink. 2+ A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder. Step S4, Microwave Carbonization Molding: The crosslinking system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in an oven at 60-80℃ and dried to constant weight. It is then ground to a particle size of 100-200 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under the conditions of microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D crosslinked molecular template organic carbon.
2. The method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates according to claim 1, characterized in that: The pulverization parameters of the flash extraction technology in step S1 are: flash extraction speed 15000 r / min, pulverization time 5-10 min.
3. The method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates according to claim 2, characterized in that: The mass ratio of K2CO3 to walnut shell molecular-level powder is 1:3-1:
5.
4. The method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates according to claim 3, characterized in that: The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:10-1:15, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:20-1:
30.
5. The method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates according to claim 4, characterized in that: Follow these steps: Step S1, Raw material pretreatment: Walnut shells are selected as biomass raw materials. After removing impurities and cleaning, they are placed in a 70℃ oven and dried to constant weight. Then, the dried walnut shells are molecularly pulverized using flash extraction technology to obtain a walnut shell molecular suspension. The flash extraction speed is 15000 r / min and the pulverization time is 8min. Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular-level suspension obtained in step S1. The mass ratio of K2CO3 to walnut shell molecular-level powder is 1:
4. Stir and mix in a constant temperature environment of 30℃ for 15 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder. Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:12, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:
25. The mixture is stirred for 45 minutes at 30°C and a stirring rate of 250 r / min to allow the FeSO4 solution to crosslink with the walnut shell molecular-level powder to form a crosslinked structure. 2+ A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder. Step S4, Microwave Carbonization Molding: The cross-linked system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in a 70°C oven to dry to constant weight and ground to a particle size of 150 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D cross-linked molecular template organic carbon.
6. The method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates according to claim 4, characterized in that: Follow these steps: Step S1, Raw material pretreatment: Walnut shells are selected as biomass raw materials. After removing impurities and cleaning, they are placed in a 60℃ oven and dried to constant weight. Then, the dried walnut shells are molecularly pulverized using flash extraction technology to obtain a walnut shell molecular suspension. The flash extraction speed is 15000 r / min and the pulverization time is 5min. Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular-level suspension obtained in step S1. The mass ratio of K2CO3 to walnut shell molecular-level powder is 1:
3. Stir and mix in a constant temperature environment of 25°C for 10 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder. Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:10, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:
20. The mixture is stirred for 30 minutes at 25°C and a stirring rate of 200 r / min to allow the FeSO4 solution to crosslink with the walnut shell molecular-level powder to form a crosslinked structure. 2+ A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder. Step S4, Microwave Carbonization Molding: The crosslinking system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in a 60°C oven to dry to constant weight and ground to a particle size of 100 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D crosslinked molecular template organic carbon.
7. The method for preparing organic carbon using microwave-assisted 3D cross-linked molecular templates according to claim 4, characterized in that: Follow these steps: Step S1, Raw material pretreatment: Walnut shells are selected as biomass raw materials. After removing impurities and cleaning, they are placed in an 80℃ oven to dry to constant weight. Then, the dried walnut shells are molecularly pulverized using flash extraction technology to obtain a walnut shell molecular suspension. The flash extraction speed is 15000 r / min and the pulverization time is 10 min. Step S2, Protonation and Crosslinking Site Pretreatment: Add K2CO3 solution to the walnut shell molecular-level suspension obtained in step S1. The mass ratio of K2CO3 to walnut shell molecular-level powder is 1:
5. Stir and mix in a constant temperature environment of 35℃ for 20 min to allow K2CO3 to undergo a protonation reaction with the hydrophilic active groups in the walnut shell powder. Step S3, 3D Crosslinking Structure Construction: FeSO4 solution is added dropwise to the protonated mixture from step S2, and the mixture is stirred until homogeneous. Then, the target pollutant benzothiophene is added, and the mixture is placed in a constant-temperature stirrer. The mass ratio of FeSO4 to walnut shell molecular-level powder is 1:15, and the mass ratio of benzothiophene to walnut shell molecular-level powder is 1:
30. The mixture is stirred for 60 minutes at 35°C and a stirring rate of 300 r / min to allow the FeSO4 solution to crosslink with the walnut shell molecular-level powder to form a 3D crosslinked structure. 2+ A three-dimensional network cross-linked structure is formed by coordination and cross-linking of the phenolic hydroxyl and carboxyl groups exposed in the walnut shell powder. Step S4, Microwave Carbonization Molding: The crosslinking system obtained in step S3 is filtered, and the filter residue is washed with deionized water until the washing liquid is neutral. Then, the filter residue is placed in an 80°C oven to dry to constant weight and ground to a particle size of 200 mesh to obtain precursor powder. The precursor powder is placed in a microwave reactor and subjected to microwave carbonization treatment under microwave power of 1000W and microwave irradiation time of 1min to obtain microwave-assisted 3D crosslinked molecular template organic carbon.
8. The application of microwave-assisted 3D cross-linked molecular templates for organic carbon, characterized by: Follow these steps: Step D1, Targeted Adsorption and Removal: The microwave-assisted 3D cross-linked molecular template organic carbon prepared according to any one of claims 1-7 is filled into the adsorption column. The coke oven gas is controlled to pass through the adsorption column at a flow rate of 1-3 mL / min, the adsorption temperature is 25-35℃ and the pressure is atmospheric pressure. The benzothiophene in the coke oven gas is targeted and adsorbed by the active adsorption sites on the surface of the biochar through the molecular channels reserved by the molecular template, thereby achieving the removal of organic sulfur in the coke oven gas. Step D2, Adsorbent Regeneration: When the microwave-assisted 3D cross-linked molecular template organic carbon reaches adsorption saturation, the coke oven gas is stopped. The microwave reactor is connected to the adsorption column, and the saturated biomass carbon in the adsorption column is irradiated with 1000W microwave for 1-2 minutes. The strong absorption performance of Fe ions on microwaves is used to rapidly raise the local temperature of the biomass carbon to 200-300℃, removing the benzothiophene adsorbed on the surface of the biomass carbon. The removed benzothiophene is recovered by condensation, realizing resource recycling. Step D3, Recycling: After regeneration is complete, microwave irradiation is stopped. After the adsorption column cools to room temperature, coke oven gas is introduced again, and steps D1-D2 are repeated to achieve multiple recycling of organic carbon from microwave-assisted 3D cross-linked molecular templates.
9. The application of the microwave-assisted 3D cross-linked molecular template organic carbon according to claim 8, characterized in that: In step 1, the ratio of the amount of organic carbon filling the microwave-assisted 3D cross-linked molecular template to the amount of coke oven gas processed is 1g:50-100L.